PINJAM PAKAI KAWASAN HUTAN DAN REALISASI PEMANFAATANNYA OLEH PT. MAHAKAM SUMBER JAYA DI KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR - Syaprudin, Ismail Bakrie dan Legowo Kamarubayana (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
This study aims to determine the actual utilization of forest use borrowed by coal mining company PT Mahakan Sumber Jaya and to determine the implications of the application of the rules of forest use in coal mining systems and various aspects of land use and forest areas that have put the loan to a third party. Companies selected in this study are located in the Kutai regency, namely PT Mahakam Sumber Jaya to wear borrowed acreage is approximately 2925.4 hectares. The selection is based on the availability of data that can be analyzed as well as one of the coal mining company that has been carrying out mining and reclamation in some areas has been completed exploited.The method used is the Survey Methods and techniques of data collection is a combination of several methods is by questionnaires, interviews, library research and documentation.  Questionnaires and interview techniques are used to complement the primary data and secondary data and documentation that has been done.  While the literature is used to collect literature and supporting materials used to construct the initial research plan. The material collected in the form of the results of similar studies, activity reports and other materials relating to the study.  The survey results revealed that the utilization of forest area lend use by PT Mahakam Jaya Lestari has been realized almost entirely, ie 92.70%, and the utilization of forest area or lease area by PT Mahakam Jaya Lestari in accordance with the provisions of the Regulation of the Minister of Forestry of the Republic of Indonesia Number P.38/Menhut-II/2012 About Guidelines Borrow and Use of Forest Area.  Reclamation and revegetation activities in stage I and II has been well realized, with over 80% success.  A small part of the area of the former coal extraction tanbang closure yet again.